MICROSPHERE A DRUG DELIVERY SYSTEM–A REVIEW - DAS, MANOJ KUMAR; AHMED, ABDUL BAQUEE; SAHA, DIPANKAR (International Journal of Current Pharmaceutical Research, 2019)
The targeted drug delivery is designed for endeavoring to concentrate the drug in the tissues of curiosity while reducing relative concentration of medication in the remaining tissues. There for drug is localized on the targeted site. Hence, surrounding tissues are not affected by the drug. Controlled drug delivery system can overcome the problems of conventional drug therapy and gives better therapeutic efficacy of a drug. Microspheres are characteristically free flowing powders consisting of proteins or synthetic polymers having a particle size ranging from 1-1000 µm. The range of Techniques for the preparation of microspheres offers a Variety of opportunities to control aspects of drug administration and enhance the therapeutic efficacy of a given drug. There are various approaches in delivering a therapeutic substance to the target site in a sustained controlled release fashion. Microspheres has a drug located centrally within the particle, where it is encased within a unique polymeric membrane. In future various other strategies, microspheres will find the central place in novel drug delivery, particularly in diseased cell sorting, diagnostics, gene and genetic materials, safe, targeted and effective in vivo delivery and supplements as miniature versions of diseased organ and tissues in the body.